3 - x = 4x - 2
3 = 5x - 2
5 = 5x
x = 1
2007-01-07 14:49:56
·
answer #1
·
answered by amateur_mathemagician 2
·
2⤊
0⤋
If question is ‘ ??-x+3=4x-2?’
This equation holds true only in following two cases:
1. ? = 1; x =7
2. ? = 6; x = 19
1. 11 – 7 + 3 = (4 x7) -21
4+3 = 28 -21
7 = 7
2. 66 – 19+3 = (4 x 19) -26
47+3 = 76 -26
50 = 50
If question is ‘-x+3 = 4x-2’
-x+3 = 4x - 2
+3 = 4x+x-2
3+2 = 5x
5 = 5x
thus x=1
2007-01-08 00:20:56
·
answer #2
·
answered by saritha devi a 1
·
0⤊
0⤋
This is an equation. You can do anthing to it as long as you do the same thing to both sides.
First you need to isolate the x variable on one side of the equation. You do this by doing the opposite mathematical operation to both sides of the equation so that x is then by itself.
-x + 3 = 4x - 2
-x + 3 + x = 4x - 2 + x
This gives you:
3 = 5x - 2
Next, get rid of the -2 by adding 2 to both sides:
3 + 2 = 5x - 2 + 2
This now gives you:
5 = 5x
To find "x", divide both sides by 5:
then, x = 1
To check your answer, insert "1" in the place of "x" and work the problem. If your answer for x is correct, then both sides will be equal.
-(1) + 3 = 4(1) - 2
-1 + 3 = 4 - 2
2 = 2
Homework done!
Good luck!
2007-01-07 23:05:37
·
answer #3
·
answered by CAROL P 4
·
0⤊
0⤋
-x + 3 = 4x - 2
3 - x = 4x - 2
3 = 5x - 2
5 = 5x
x = 1
2007-01-10 04:31:18
·
answer #4
·
answered by Kinu Sharma 2
·
0⤊
0⤋
Algebra
Problem
-x+3=4x-2
Add x to both sides of equasion
x-x+3=4x-2+x
Simplify
3=5x-2
Add 2 to both sides of equasion
2+3=5x-2+2
Simplify
5=5x
Multiply by 1/5 to both sides of equasion
(1/5)(5)=(1/5)(5x)
simplify
1=x
Prove to verify
-x+3=4x-2
Where x=1
-1+3=4(1)-2
2=4-2
Simplfy
2=2
2007-01-07 23:05:18
·
answer #5
·
answered by Gary M 3
·
0⤊
0⤋
3 - x = 4x - 2
3 = 5x - 2
5 = 5x
x = 1
2007-01-08 01:47:17
·
answer #6
·
answered by srikant s 1
·
0⤊
0⤋
-x+3=4x-2
2+3=4x+x
5=5x
1=x
Group the like numbers together. In order to do that you must invert the number when you move them from one side of the equal sign to the other. Once you have group like numbers together and solved that part of the equation you then break the problem down to the lowest possible demoninator.
2007-01-07 23:02:10
·
answer #7
·
answered by Kelly M 1
·
0⤊
0⤋
-x+3=4x-2
+x +x
3=5x-2
+2 +2
5=5x
/5 /5
1=x
2007-01-07 22:58:59
·
answer #8
·
answered by amanda d 1
·
0⤊
0⤋
substitute x=0.
0+3=0-2
=> 3=-2 which is false
again substitute x=1
=>1+3=4-2
=> 2=2
which is true
then x=1
2007-01-07 23:02:17
·
answer #9
·
answered by The Prince of Egypt 5
·
0⤊
0⤋
-x+3=4x-2
3+2=4x+x
5=5x or
5x=5
x=5/5
x=1
2007-01-08 01:08:33
·
answer #10
·
answered by munni 1
·
0⤊
0⤋